An Intervention to Increase 24-Hour Urine Collection Compliance. Issue 1 (January 2019) - Boyd, Carter; Wood, Kyle; Ashorobi, Omotola; Harvey, Lisa; Oster, Robert; Holmes, Ross P.; Assimos, Dean G.
Abstract: Introduction: Compliance with 24-hour urine collections for assessing kidney stone risk is important in assigning preventive therapy. We determined factors associated with compliance and the impact of an intervention. Methods: In 2015 those patients requiring 24-hour urine testing were instructed to contact the vendor (Litholink®) and were given instructions by the same nurse to arrange for collections. In 2016 a practice change was implemented and all requests were sent directly to the vendor by FAX. In both years combined (2015/2016), 24-hour urine studies were ordered for 368 adult stone formers. Demographic data included age, gender, race, insurance status, partner status, income and education. Statistical methods included ANOVA, Fisher's exact test, chi-square test and t-test. Compliance was based on completion of 24-hour urine collections. Data were analyzed for 2015, 2016 and both years combined. Results: Average stone former age was 49.6 years at the time of collection. Overall 47.5% were female, 84.2% were Caucasian and 15.8% were African American. Most patients were adequately insured (90.5%) and had domestic partners (61.4%). Compliance increased from 46.9% to 65.1% after the intervention (p <0.001). Adequate insurance was associated with increased compliance for both years combined (58.3% vs 37.15%, p=0.017). Partner status and older age were associated with increased compliance in 2015 (54.2% vs 32.8%, p=0.006; 52.9 vs 47.1 years, p=0.014, respectively), but after intervention in 2016 they were no longer contributing factors. Conclusions: An intervention was associated with an increase in compliance of 18% and the elimination of health disparities (age, partner status). Inadequate insurance status resulted in poor compliance despite this intervention.